Papua New Guinea : Staff Report for the 2013 Article IV Consultation. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2013)
This 2013 Article IV Consultation highlights that Papua New Guinea has achieved strong economic growth over the past decade, benefiting from high commodity prices, mineral investment inflows, sound macroeconomic policies, and financial sector stability. The current account deficit is expected to narrow sharply in 2013 as imports and income outflows decline with the winding down of liquefied natural gas project construction. The Bank of Papua New Guinea has kept the policy interest rate unchanged since early 2013 given weakening nonmineral sector demand, but has issued central bank bills and raised cash reserve requirements to absorb excess liquidity in the banking system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet